Situação profissional dos licenciados em gestão e desenvolvimento social pela ucp - pólo de Viseu - Paulo Almeida Pereira (Gestão e Desenvolvimento)
Without using an elaborate statistical analysis, this article aims to present briefly the employment situation of the graduates on Management and Social Development, from the University Institute of Development and Social Promotion (UIDSP) - Portuguese Catholic University (PCU) in Viseu, during the academic years of 1995/96, 1996/97 and 1997/98. The analysis focuses essentially on the unemployment rate and the time graduates wait to find a job. lt also focuses on the employment distribution by activity and the relevant differences among the graduates through the various academic years. The assessment of these parameters shows good job opportunities for the graduates on Management and Social Development